(Invited) SOI Technologies for RF and Millimeter Wave Applications. (3rd July 2019) - Rack, Martin; Raskin, Jean-Pierre
Abstract : In this paper, an overview of SOI technology for high-frequency telecommunication applications is presented. At the transistor level, thanks to SOI's low-parasitic architecture and good electrostatics, high oscillation and cut-off frequencies in the range of 400 GHz are achieved. At the RF-IC level, a review is made to reveal the position of SOI for key RF and millimeter wave circuits (switches, LNAs and PAs). Finally, substrate impact is described at RF frequencies. The existing flavors of SOI substrates are reviewed, highlighting substrate requirements at RF, as it seriously impacts parasitic coupling, RF losses, passive quality factor, and non-linear signal distortion. Overall, SOI is shown to be a prime candidate not only for high-performance millimeter wave and 5G applications, but also for low-power RF IoT.